Tejeduría en fique (2021)
The fique is an extraordinary material, which is part of the tradition of the fiquera and artisan population of Curití Santander,the objective of this project was to develop a catalog of possibilities at an aesthetic and productive level, where it is evident the expe- rience and capacity of the artisans, the value chain is strengthened; in addition to reaching new markets, creating a differentiation from other communities and attract people from the creative sector who want to immerse themselves in the technique andexploit its potential. This population of artisans is made up of around 154 artisans whose main source of income is the weaving in fique, for this project an investigation was carried out on the material, its production processes for its subsequent tissue, immediately nine development proposals were made for the fique design, (Brightness, transparency and volume), which propose structures, together with the combination of materials, finally, the nine proposals based on the different testing techniques.